Morphological and physiological variation of soybean seedlings in response to shade - Wu, Yushan; Chen, Ping; Gong, Wanzhuo; Gul, Hina; Zhu, Junqi; Yang, Feng; Wang, Xiaochun; Yong, Taiwen; Liu, Jiang; Pu, Tian; Yan, Yanhong; Yang, Wenyu (Frontiers in Plant Science, 2022)
Soybean (Glycine max) is a legume species that is widely used in intercropping. Quantitative analyses of plasticity and genetic differences in soybean would improve the selection and breeding of soybean in intercropping. Here, we used data of 20 varieties from one year artificial shading experiment and one year intercropping experiment to characterize the morphological and physiological traits of soybean seedlings grown under shade and full sun light conditions. Our results showed that shade significantly decreased biomass, leaf area, stem diameter, fraction of dry mass in petiole, leaf mass per unit area, chlorophyll a/b ratio, net photosynthetic rate per unit area at PAR of 500μmol m-2 s-1 and 1200 μmol m-2 s-1 of soybean seedling, but significantly increased plant height, fraction of dry mass in stem and chlorophyll content. Light ×variety interaction was significant for all measured traits, light effect contributed more than variety effect. The biomass of soybean seedlings was positively correlated with leaf area and stem diameter under both shade and full sunlight conditions, but not correlated with plant height and net photosynthetic rate. The top five (62.75% variation explained) most important explanatory variables of plasticity of biomass were that the plasticity of leaf area, leaf area ratio, leaflet area, plant height and chlorophyll content, which whose total weight were 1, 0.9, 0.3, 0.2, 0.19, respectively. The plasticity of biomass was positively correlated with plasticity of leaf area and leaflet area but significant negative correlated with plasticity of plant height. A total of 62.75% variation explained by the top five explanatory variables and the The principal component one account for 42.45% variation explain. A cluster analysis further indicated that soybean cultivars were classified into three groups and cultivars; Jiandebaimaodou3, Gongdou 213, and Guixia 320 with the maximum plasticity of biomass. These results suggest that for soybean seedlings grown under shade increasing the capacity for light interception by larger leaf area is more vital than light searching (plant height) and light conversion (photosynthetic rate).